2007
DOI: 10.4314/sajas.v37i4.4100
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of testicular development with age, body weight, semen characteristics and testosterone in Kivircik ram lambs

Abstract: The study was conducted to measure the development of several testicular characteristics and to investigate the relationship between testicular parameters with body growth, semen characteristics and serum testosterone levels in growing ram lambs. Seventeen single born Kivircik ram lambs from three to four year old ewes were used. When the rams were two months old measurements of the length, diameter and circumference of their testes and body weights started, and blood samples were collected at 20-day intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
14
17
0
Order By: Relevance
“…Ultrasound examination for interpreting uncertain clinical findings or for detecting early stages of pathological processes in ram genitalia is very important for the complete reproductive assessment (Gouletsou et al, 2003;Gouletsou and Fthenakis, 2010;Ahmadi et al, 2013;Saaed and Zaid, 2018). The mean values of scrotal circumference in both categories rams (18.8 ± 5.9 cm and 30.7 ± 4.4 cm) were close to values for young Synthetic Population Bulgarian Milk rams (23.7 ± 0.4 cm) and mature Kivircik animals (30.24 ± 0.91 cm), reported by Elmaz et al (2007) and Metodiev et al (2014), respectively. However, no correspondence was observed with the results (29.23 ± 3.32 cm and 33.23 ± 1.60 cm) in pubertal and sexually mature Santa Ines rams (Ribeiro et al, 2017) or the records (31.8 ± 0.4 cm and 33.3 ± 0.5 cm) for peri-and postpubertal Dorper rams (Camela et al, 2019).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 62%
See 1 more Smart Citation
“…Ultrasound examination for interpreting uncertain clinical findings or for detecting early stages of pathological processes in ram genitalia is very important for the complete reproductive assessment (Gouletsou et al, 2003;Gouletsou and Fthenakis, 2010;Ahmadi et al, 2013;Saaed and Zaid, 2018). The mean values of scrotal circumference in both categories rams (18.8 ± 5.9 cm and 30.7 ± 4.4 cm) were close to values for young Synthetic Population Bulgarian Milk rams (23.7 ± 0.4 cm) and mature Kivircik animals (30.24 ± 0.91 cm), reported by Elmaz et al (2007) and Metodiev et al (2014), respectively. However, no correspondence was observed with the results (29.23 ± 3.32 cm and 33.23 ± 1.60 cm) in pubertal and sexually mature Santa Ines rams (Ribeiro et al, 2017) or the records (31.8 ± 0.4 cm and 33.3 ± 0.5 cm) for peri-and postpubertal Dorper rams (Camela et al, 2019).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 62%
“…An evidence for this suggestion was no collected semen from two younger animals in the first group by electroejaculation method. The positive correlation between VE and CS may be related to better hormonal stimulation of the sperm producing tissue and development of the accessory glands in sexually mature animals (Elmaz et al, 2007;Ribeiro et al, 2017).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 97%
“…Testicular dimension and size of the ram lamb can be used as criteria for early selection of ram lambs to be used in breeding at relatively younger age (Elmaz et al, 2007). Moreover, reproductive activity of rams is dependent and significantly correlated with postweaning growth and size of the testes (Elmaz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that there are significant positive correlations between testicle measurements and seminal traits in young seven to eight month old rams (ELMAZ et al, 2007). So, this information may be used as criteria for early selection of ram lambs to be used in breeding at relatively young ages (ELMAZ et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…These body measurements have been used at various times for the estimation of weight (YILMAZ et al, 2013), breed characterization and differentiation (YAKUBU;IBRAHIM, 2011), and for early selection of ram lambs (ELMAZ et al, 2007). As regards testicular-epididymal biometry, some studies have demonstrated that body weight may be reflected in testicle size (DUGUMA et al, 2002), because the heritability between scrotal circumference and testis diameter is moderate to high.…”
Section: Introductionmentioning
confidence: 99%